Modified Lamport Merkle Digital Signature blockchain framework for authentication of internet of things healthcare data. Issue 10 (12th March 2022) - Mehbodniya, Abolfazl; Webber, Julian L.; Neware, Rahul; Arslan, Farrukh; Pamba, Raja Varma; Shabaz, Mohammad
Abstract: Medical internet of things (IoT) includes various devices, sensor, machines, equipment which exchange data over wide network. Industry 5.0 and 5G technology have ramped mIoT data and cost‐effective sensors. There is sudden upsurge in the medical IoT for enhancing the medical care. Integration of cloud server for data storage and cloud computing has led to the emergence of time and cost‐effective management of medical resources and improved patient lifestyle. However, cloud data is always at risk of data leak and malicious attack by unwanted users for their personal gains and agenda. With the increase of data exchange in the medical field, there is an urgency of keeping all the transaction safe and secure. There is a growing malicious data attacks and vulnerability. Therefore, to overcome such situations, the proposed model is a step towards sustainable technology. Keeping the focus on cost effective data security, the present work has developed a framework of modified Lamport Merkle Digital Signature method for signature generation and verification. It makes use of central healthcare controller (CHC) which determine the root of generated signature along with verification and authentication. For verification, the validation hash public key with generate key is required to validate the signature. This led to the efficient, cost effective and faster security when compared to the existing methods.